2024
DOI: 10.1021/acs.jafc.4c01622
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarum-Derived Indole-3-lactic Acid Ameliorates Intestinal Barrier Integrity through the AhR/Nrf2/NF-κB Axis

Arong Wang,
Cheng Guan,
Tieqi Wang
et al.

Abstract: Our previous studies have shown that Lactiplantibacillus plantarum DPUL-S164-derived indole-3-lactic acid (ILA) ameliorates intestinal epithelial cell barrier injury by activating aryl hydrocarbon receptor (AhR) and nuclear factor erythroid 2related factor 2 (Nrf2) signaling pathways and promoting tight junction protein expression. This study further explored the crucial substances of L. plantarum DPUL-S164 in alleviating intestinal barrier damage in mice through a dextran sodium sulfate-induced ulcerative col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…pylori were also down-regulated by ILA. Extensive reports have demonstrated that indole metabolites can effectively mitigate gastrointestinal injury caused by stress, suppress pro-inflammatory pathways, and boost anti-inflammatory pathways. , In the intestine, ILA has been shown to mitigate inflammation in epithelial cells by downregulating IL-8 levels as well as reduce mucosal inflammation in mice by suppressing TNF-α and IL-6 expression . Furthermore, pretreatment with ILA effectively inhibited ultraviolet B (UVB)-induced production of IL-6 in HaCaT human keratinocytes .…”
Section: Discussionmentioning
confidence: 99%
“…pylori were also down-regulated by ILA. Extensive reports have demonstrated that indole metabolites can effectively mitigate gastrointestinal injury caused by stress, suppress pro-inflammatory pathways, and boost anti-inflammatory pathways. , In the intestine, ILA has been shown to mitigate inflammation in epithelial cells by downregulating IL-8 levels as well as reduce mucosal inflammation in mice by suppressing TNF-α and IL-6 expression . Furthermore, pretreatment with ILA effectively inhibited ultraviolet B (UVB)-induced production of IL-6 in HaCaT human keratinocytes .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al , reported that Lactobacillus-derived indole lactic acid could promote the expression of key bacterial enzymes implicated in tryptophan metabolism, leading to the synthesis of other indole derivatives including indole-3-propionic acid and indole-3-acetic acid, possessing the ability to reduce colonic inflammation. Anticolitis effect of indole lactic acid was also shown in previous studies conducted by Li et al and Wang et al Moreover, anti-inflammation effect of indole-3-carboxaldehyde has been recently recognized. Indole-3-carboxaldehyde has been shown to alleviate inflammation in the colon, liver, and kidney. , Although mechanisms underlying the benefits of indole derivatives remain exclusive, they may act as key PXR-modulating activators, subsequently attenuating inflammation by inhibiting NF-κB signaling. …”
Section: Discussionmentioning
confidence: 99%